Pathology and systemic therapy of non-clear cell renal cell carcinoma: an overview. Issue 11 (2nd November 2021) - Bergmann, Lothar; Weber, Sarah; Hartmann, Arndt; Ahrens, Marit
ABSTRACT: Introduction: Non-clear cell renal cell carcinoma (nccRCC) represents a highly heterogenous group of kidney cancer entities. As most clinical trials predominantly include patients with clear cell RCC (ccRCC), nccRCC treatment guidelines are mainly extrapolated from recommendations in ccRCC. Here, we review and elucidate current data on the pathologic classification and treatment of nccRCC. Areas covered: This article gives an overview of the WHO classification of RCC, showing the histological diversity of nccRCC and focusing particularly on entities first characterized since 2016, their specific molecular behavior and their role as indicators for hereditary cancer syndromes. In this context, we discuss the available data on nccRCC treatment oprtions such as tyrosine kinase inhibitors, mammalian target of rapamycin inhibitors, cytotoxic chemotherapy, and immune checkpoint inhibitors. Expert opinion: Although nccRCCs are relatively uncommon, entities of this type account for a subgroup of up to 20–25% of all RCCs. Advances in histopathology and molecular genetics, together with evidence gained from retrospective and prospective clinical data, have improved understanding of these tumors in recent years. Nevertheless, selective trials of current and novel therapies including new targeted agents in patients with nccRCC are urgently needed to further improve treatment guidelines.